Absorption intestinale des vitamines liposolubles - Reboul Emmanuelle (Oléagineux, Corps gras, Lipides, 2011)
The molecular mechanisms of fat-soluble vitamin intestinal absorption remain partly unknown, despite the fact that a better understanding of this process would certainly allow to improve their bioavailability. If their digestion-absorption process follows the fate of lipids globally, the recent discovery of membranes proteins involved in their absorption questioned the established dogmas. These new data should be taken into account to avoid dietary or drug interactions that may limit some fatsoluble vitamin bioavailability.